2007
DOI: 10.1203/pdr.0b013e318045bec9
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Moderate and High Dietary Long Chain Polyunsaturated Fatty Acids (LCPUFA) on Baboon Neonate Tissue Fatty Acids

Abstract: Docosahexaenoic acid (DHA) and arachidonic acid (ARA) are now common ingredients in commercial infant formulas, however, the optimal levels have not been established. Our previous data showed that the current amount of DHA in U.S. term formulas, 0.3%w/w, is insufficient to normalize cerebral cortex DHA to levels in breastfed baboon neonate controls (Diau et al.: BMC Medicine 3: 11, 2005). Here, we report on the influence of higher formula DHA levels on 12-wk-old full-term baboon CNS and visceral organs. Fourt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
53
0
3

Year Published

2007
2007
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 33 publications
5
53
0
3
Order By: Relevance
“…1, panels A and C) proved different from the relation with AA. Generally, brain DHA is more sensitive to dietary DHA than brain AA is to dietary AA, which has been shown in baboons [35] and may also be derived from autopsy studies in breast and formula fed infants [36][37][38]. The descending part of the U-shaped relation between GM quality and the iRBC DHA/AA ratio (Fig.…”
Section: Discussionmentioning
confidence: 73%
See 2 more Smart Citations
“…1, panels A and C) proved different from the relation with AA. Generally, brain DHA is more sensitive to dietary DHA than brain AA is to dietary AA, which has been shown in baboons [35] and may also be derived from autopsy studies in breast and formula fed infants [36][37][38]. The descending part of the U-shaped relation between GM quality and the iRBC DHA/AA ratio (Fig.…”
Section: Discussionmentioning
confidence: 73%
“…What brain areas are involved in the ascending part of the curve might become suggested from studies in newborn baboons. These show that the brain motor areas are not only highest in DHA (and AA) contents [44], but also the most sensitive to DHA supplementation [35]. Experiments with young rats revealed that fish oil supplementation influences several neurochemical and behavioral features of monoaminergic function, causing an increase of cerebral membrane phosphatidylserine, higher dopamine, reduction of monoamineoxidase-B activity and greater binding to dopamine D2 receptors in the frontal cortex, and also lower ambulatory activity [45].…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…Our most recent studies are consistent with these observations. Importantly, they extend them by showing that dietary DHA levels of 1% do raise cerebral cortex DHA beyond that which can be achieved by lower levels [24].…”
Section: Effect Of Supplementation and Prematuritymentioning
confidence: 76%
“…In the featured work in this issue of Pediatric Research, Hsieh and colleagues, working in Tom Brenna's laboratory, demonstrated that when DHA is added to formula fed to newborn baboons in a range similar to that found in some human infant formulas (0.33 wt% theoretical and 0.42 wt% actual), that brain DHA content was significantly increased in the plasma, erythrocyte, heart, cerebral cortex (both precentral gyrus and frontal lobe), globus pallidus, caudate, and superior and inferior colliculi (10). This is consistent with previous work from this laboratory showing that DHA supplementation could largely prevent the losses in brain DHA associated with unsupplemented formulas and restore them to the breast-fed control level (11).…”
mentioning
confidence: 88%